2021
DOI: 10.1002/advs.202100249
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Generative Design for 3D Printing of Bacterial Biofilm Resistant Composite Devices

Abstract: As the understanding of disease grows, so does the opportunity for personalization of therapies targeted to the needs of the individual. To bring about a step change in the personalization of medical devices it is shown that multi‐material inkjet‐based 3D printing can meet this demand by combining functional materials, voxelated manufacturing, and algorithmic design. In this paper composite structures designed with both controlled deformation and reduced biofilm formation are manufactured using two formulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…GAs mimicthe natural selection and evolutionary process to improve certain features following a number of generations [46]. GAs have been utilised in structural optimization and design for AM in previous research [47]. To implement GA in this study, the number of generations was set to 50, population size was set to 20, the number of pairs of chromosomes to cross over in each generation was four and the number of chromosomes to be mutated in each generation was four.…”
Section: The Optimization Of the Design Through Gamentioning
confidence: 99%
“…GAs mimicthe natural selection and evolutionary process to improve certain features following a number of generations [46]. GAs have been utilised in structural optimization and design for AM in previous research [47]. To implement GA in this study, the number of generations was set to 50, population size was set to 20, the number of pairs of chromosomes to cross over in each generation was four and the number of chromosomes to be mutated in each generation was four.…”
Section: The Optimization Of the Design Through Gamentioning
confidence: 99%
“…Overall, these results corroborate previous studies, which indicated a general lack of toxicity of these polymers to fungi, bacteria and mammalian cells. 20,[39][40][41] In fact, it was noted that the total growth yield of A. pullulans within the medium was >2-fold greater in pmMAOES-or pAODMBAcoated wells when compared to the uncoated wells ( p < 0.001), suggesting the possibility that A. pullulans might use these polymers as a nutrient source. A. pullulans is known to secrete an arsenal of digestive enzymes that are effective at breaking down materials for nutrient acquisition.…”
Section: Assessment Of Polymer Performance In Resisting Fungimentioning
confidence: 99%
“…Gradients of material composition have been demonstrated previously, (He et al, 2021;Levato et al, 2020) but these are generally limited to highly digitised variations in the composition. For example, when using extrusion, (Rupp et al, 2021) it is difficult to achieve variation of composition in the case of single material extrusion and it is limited to varying infill to produce a gradient.…”
Section: Introductionmentioning
confidence: 97%